Precision oncology for RET-related tumors - Verrienti, Antonella; Grani, Giorgio; Sponziello, Marialuisa; Pecce, Valeria; Damante, Giuseppe; Durante, Cosimo; Russo, Diego; Filetti, Sebastiano (Frontiers in Oncology, 2022)
Aberrant activation of the RET proto-oncogene is implicated in a plethora of cancers. RET gain-of-function point mutations are driver events in multiple endocrine neoplasia 2 (MEN2) syndrome and in sporadic medullary thyroid cancer, while RET rearrangements are driver events in several non-medullary thyroid cancers. Drugs able to inhibit RET have been used to treat RET-mutated cancers. Multikinase inhibitors were initially used, though they showed modest efficacy and significant toxicity. However, new RET selective inhibitors, such as selpercatinib and pralsetinib, have recently been tested and have shown good efficacy and tolerability, even if no direct comparison is yet available between multikinase and selective inhibitors. The advent of high-throughput technology has identified cancers with rare RET alterations beyond point mutations and fusions, including RET deletions, raising questions about whether these alterations have a functional effect and can be targeted by RET inhibitors. In this mini review, we focus on tumors with RET deletions, including deletions/insertions (indels), and their response to RET inhibitors.